(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides an overview of the category of number in linguistics, a grammatical system that helps languages express distinctions in quantity. It begins with the widely used singular and plural forms—categories that indicate one versus more than one—and then explores additional number distinctions, such as dual (two items), trial (three items), and paucal (a few items). Singular and plural distinctions are common, with variations in how languages mark these forms. For example, English uses suffixes like “-s”, while languages like Chinese use context or quantifiers rather than morphological changes. Languages like Arabic and Slovenian use a “dual form” to express exactly two items, while some Oceanic languages feature trial and paucal distinctions, marking small groups. Some languages use collective nouns to indicate grouped items or substances that do not easily fit into countable units, such as "water" or "sand." Not all languages make grammatical number distinctions; languages like Vietnamese and Pirahã do not require singular/plural markers, relying on context or optional quantifiers instead. The article concludes by discussing how these number categories reflect cultural perspectives and cognitive priorities, providing insight into how languages shape and are shaped by human perception of quantity and individuality.